GAMBARAN FAKTOR RESIKO TERJADINYA HIPERTENSI DI WILAYAH KOTA GORONTALO - Lamangida, Sri Yuningsi; Maria Masi, Gresty Natalia; Renteng, Septriani (Universitas Sam Ratulangi, 2024)
Background: Hypertension is a cardiovascular disease and is the most prevalent health issue in society. It is often referred to as